Corporate Governance, Capital Intensity, And Tax Avoidance: Evidence From Food And Beverage Firms On The IDX (2019–2023) - Aziz, Badrun; Purwatiningsih, Purwatiningsih (Yayasan Pendidikan Penelitian Pengabdian Al-amsi, 2025)
This study investigates the influence of corporate governance mechanisms and capital intensity on tax avoidance in food and beverage companies listed on the Indonesia Stock Exchange (IDX) during 2019–2023. Corporate governance is represented by managerial ownership, institutional ownership, and independent commissioners, while capital intensity reflects investment in fixed assets. Using purposive sampling, 10 firms were selected, producing 35 panel data observations analyzed with the Fixed Effect Model (FEM). The results reveal that, partially, managerial ownership, institutional ownership, independent commissioners, and capital intensity have no significant effect on tax avoidance, but simultaneously these variables significantly influence tax avoidance, indicating that governance mechanisms and structural characteristics are more effective when considered collectively rather than individually. These findings are consistent with agency theory, which emphasizes the role of governance structures in reducing agency problems, and also support prior empirical studies in emerging markets. The study contributes by providing sector-specific evidence from the Indonesian food and beverage industry and offers practical insights for managers, investors, and regulators to strengthen governance frameworks, limit opportunistic tax practices, and ensure sustainable corporate compliance.